Elevated red blood cell distribution width contributes to poor prognosis in patients undergoing resection for nonmetastatic rectal cancer. Issue 3 (January 2018) - Zhang, Xubing; Wu, Qingbin; Hu, Tao; Gu, Chaoyang; Bi, Liang; Wang, Ziqiang
Abstract : Abstract: Several studies have reported that elevated red blood cell distribution width (RDW) was associated with the poor prognosis of different kinds of cancers. The aim of this study was to investigate the prognostic role of RDW in patients undergoing resection for nonmetastatic rectal cancer. We retrospectively reviewed a database of 625 consecutive patients who underwent curative resection for nonmetastatic rectal cancer at our institution from January 2009 to December 2014. The cutoff value of RDW was calculated by receiver-operating characteristic curve. The results demonstrated that patients in high RDW-cv group had a lower overall survival (OS) ( P  = .018) and disease-free survival ( P  = .004). We also observed that patients in high RDW-sd group were associated with significantly lower OS ( P  = .033), whereas the disease-free survival (DFS) was not significantly different ( P  = .179). In multivariate analysis, we found elevated RDW-cv was associated poor DFS (hazard ratio [HR] = 1.56, P  = .010) and RDW-sd can predict a worse OS (HR = 1.70, P  = .009). We confirmed that elevated RDW can be an independently prognostic factor in patients undergoing resection for nonmetastatic rectal cancer. So more intervention or surveillance might be paid to the patients with nonmetastatic rectal cancer and elevated RDW values in the future.